Mechanical and Metallurgical Properties of Various Nickel-Titanium Rotary Instruments. (28th November 2017) - Shim, Kyu-Sang; Oh, Soram; Kum, KeeYeon; Kim, Yu-Chan; Jee, Kwang-Koo; Chang, Seok Woo
Abstract : The aim of this study was to investigate the effect of thermomechanical treatment on mechanical and metallurgical properties of nickel-titanium (NiTi) rotary instruments. Eight kinds of NiTi rotary instruments with sizes of ISO #25 were selected: ProFile, K3, and One Shape for the conventional alloy; ProTaper NEXT, Reciproc, and WaveOne for the M-wire alloy; HyFlex CM for the controlled memory- (CM-) wire; and TF for the R-phase alloy. Torsional fracture and cyclic fatigue fracture tests were performed. Products underwent a differential scanning calorimetry (DSC) analysis. The CM-wire and R-phase groups had the lowest elastic modulus, followed by the M-wire group. The maximum torque of the M-wire instrument was comparable to that of a conventional instrument, while those of the CM-wire and R-phase instruments were lower. The angular displacement at failure (ADF) for the CM-wire and R-phase instruments was higher than that of conventional instruments, and ADF of the M-wire instruments was lower. The cyclic fatigue resistance of the thermomechanically treated NiTi instruments was higher. DSC plots revealed that NiTi instruments made with the conventional alloy were primarily composed of austenite at room temperature; stable martensite and R-phase were found in thermomechanically treated instruments.